La coordinación óculo-manual en la recepción del ecuavoley - Chuqui Chicaiza, José Luis (2022)
The present investigation consisted in proposing a guide for "Oculo-manual coordination in the reception of the Ecuavoley" in which strategies are proposed that allow to improve shortcomings in terms of the coordination technique in the aforementioned ages, establishing that the training of the students in Ecuavoley is very broad and that there are essential areas that are pillars of a quality player such as coordination and balance related to recreational exercises for the fundamental development of the reception technique in Ecuavoley. The main objective was to improve eye-hand coordination in the reception of the Ecuavoley in first-year high school students of Metal Constructions of the Educational Unit Licto school year 2021-2022. On the other hand, it was determined how hand-eye coordination influences the Ecuavoley reception technique in 14- and 15-year-old students from the "Licto" Educational Unit, which was constituted as the sample. A test and observation sheet were used as an instrument for the present investigation, taking into account their physical condition and the coordination they must develop to be able to participate in this popular sport such as Ecuavoley. The development of this research aims to offer a didactic guide of exercises that will help improve reception, which in my opinion is one of the main technical gestures that should be taught. A didactic guide of coordination and playful exercises focused on the technical progress of the reception of the Ecuavoley was designed for the first-year high school students Metallic Constructions of the Licto Educational Unit, where the students will be able to carry out different exercises oriented to the improvement of coordination. It was concluded that, when carrying out the evaluation of the pre-test and the record, 65% of the students fit with an irregular activity, while after the application of the post-test and the record the students reach 60.7% activity. good and only 39.3% remain regular.